Technological peculiarities of the content of the Aberdin-Angussian bread in the winter period at the open sites - Колісник, О. І.; Прудніков, В. Г.; Криворучко, Ю. І.; Нагорний, С. А. (Scientific Progress & Innovations, 2017)
The questions of the necessity of adjusting some parameters of the meat cattle breeding technology taking into account the influence of the natural and climatic conditions during cattle maintenance during the winter period at the feeding and feeding areas without the use of capital facilities are considered. The Aberdin-Angussian breed is well adapted to the effects of low temperatures, but in winter precipitation in the form of rain and wet snow with a cold wet wind adversely affect on the growth rate of animals. To prevent the decrease in the productivity of animals, it is necessary to increase the introduction of the amount of straw litter and hay per one animal to 7 kg per day, to increase the energy supply of the ration by increasing the amount of concentrates. At critically low temperatures it is more expedient to include in the diet bulky fodder with less moisture, i.e. soilage, which are more technological at eating.